Assessment the horizontal micro-tunnelling discharge for torrents in Buraydah city, Al-Qassim region - Al-Rashidi, Fihan Mamdouh Saud (Journal of natural sciences, life and applied sciences, 2023)
The study aimed to understand the spatial relationship between the heavy water collection points and the valleys entering the city of Buraidah, and to evaluate the torrential drainage networks that carry the torrents in the city of Buraidah. To achieve the objectives of the study, the descriptive analytical approach was used to identify the natural torrential water gathering points and the valleys entering the city of Buraidah using satellite visualizations and hydrological maps. The field study was also used to determine the collection points of torrential waters (lakes) and to track the drainage networks that carry torrential torrents and analyze them using systems programs. Geographic information. The study proved several results, the most important of which is that the collection points of torrential waters (lakes) are 18 points, one lake is located within the scope of natural water collection, while seven points are located within the hydrological network of the island. There are valleys that enter the city of Buraydah and ten points that have nothing to do with the valleys and where natural water does not accumulate. As it turned out from the study, the torrential drainage networks in Al-Fayiziyah and Al-Rabiah are the most harmful, especially the Al-Rabieh neighborhood, and the torrential drainage networks in the Northern Ring Road and the Prince Nayef flow to Al-Wasit. Valley, and so the water goes to the neighborhoods of lavender, roses, hillock and green. The study recommends linking the torrential drainage networks of Al-Fayiziyah, Al-Rabieh, the Northern Ring Road and Prince Nayef by linking them to the western and Gulf torrential drainage networks to flow into Wadi Al-Ruma. Establishment of rainwater collection points (lakes) in Al-Khuzama, Al-Rabieh and Al-Rabieh neighborhoods. Stopping the urban sprawl towards Wadi Al-Watti.